2004
DOI: 10.1038/sj.bjc.6601762
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with HIV-related germ cell tumours: a case–control study

Abstract: Testicular germ cell tumour (GCT) is not an AIDS-defining illness despite an increased incidence in men with HIV infection. We performed a matched case-control study comparing outcomes in HIV-positive men and the general population with GCT, using three age and stage matched controls for each case. There was no difference in the 5-year GCT-free survival between cases and controls. However, overall survival was significantly decreased in the cases (log rank P ¼ 0.03). HIV was responsible for 70% of this mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…Certain environmental factors have been suggested to be involved in aetiology including occupational exposures to oestrogenic chemicals and maternal exposures to chemicals including polychlorinated biphenyls, hexachlorobenzene and chlordanes [30][31][32][33]. Some studies have postulated a link with infections, including the human immunodeficiency virus (HIV), cytomegalovirus (CMV), Epstein-Barr virus (EBV) and Simian virus-40 (SV-40) [34][35][36][37][38]. Exposure to these and other putative environmental factors is likely to be socially determined.…”
Section: Discussionmentioning
confidence: 99%
“…Certain environmental factors have been suggested to be involved in aetiology including occupational exposures to oestrogenic chemicals and maternal exposures to chemicals including polychlorinated biphenyls, hexachlorobenzene and chlordanes [30][31][32][33]. Some studies have postulated a link with infections, including the human immunodeficiency virus (HIV), cytomegalovirus (CMV), Epstein-Barr virus (EBV) and Simian virus-40 (SV-40) [34][35][36][37][38]. Exposure to these and other putative environmental factors is likely to be socially determined.…”
Section: Discussionmentioning
confidence: 99%
“…In a matched case-control study comparing HIV-infected and HIV-negative patients with GCC, there was no difference in the cancer-free survival between both groups [27]. By contrast, the overall survival of the HIV-infected cohort was significantly decreased when compared to the HIV-negative group with 2-and 5-year actuarial survival rates of 94% and 76% for HIV-infected patients compared to 94% and 90% for HIV-negative patients.…”
Section: Presentation and Prognosismentioning
confidence: 99%
“…The relapse-free survival for stage I patients treated with orchidectomy and surveillance is not affected by HIV status, so that patients with stage I seminoma can be safely managed with surveillance [24,27]. It appears 3 cycles of cisplatin, etoposide, bleomycin (BEP) suppresses the CD4 cell count by between 25 and 50%, and it is probable that 1-2 cycles of BEP will also be suppressive [29].…”
Section: Treatmentmentioning
confidence: 99%
“…Initial studies suggested that patients with HIV-related cancer had worse outcome compared to those who were HIV negative due to high mortality for opportunistic infections such as Pneumocystis Carinii pneumonia, less tolerance to chemotherapy regimen resulting in treatment discontinuation and lower response rate and lastly a more aggressive behavior of GCT due to an intrinsic chemotherapy resistance [16]. However no prospective randomized clinical trial are available to explore prognosis, clinical outcome and oncological management for HIV-positive patients with testicular cancer, so decision making is often based on large retrospective series.…”
Section: Discussionmentioning
confidence: 99%